Empowerment of Digital Technology for the Resilience of the Logistics Industry: Mechanisms and Paths - Zhang, Jifeng; Yang, Zirui; He, Bing (Systems (Basel), 2024)
Digital technology, acting as an engine for industrial development, propels the rapid integration of data elements and the swift iteration of digital logistics technology, significantly enhancing logistic resilience. Exploring the impact of digital technology on the resilience of logistics helps strengthen the latter’s ability to withstand external shocks. Based on the correlation between digital technology and the resilience of the logistics industry, this study measured their levels in 275 Chinese prefecture-level cities from 2011 to 2020, showing that the former significantly improved the latter, a conclusion which remained valid after robustness tests. The mechanism analysis results showed that promoting industrial collaborative agglomeration was an important part of this process, while the threshold model analysis found that the impact on resilience had nonlinear characteristics. The heterogeneity test results showed that digital technology had a significant resilience-promoting effect in the eastern and northern coastal regions, as well as in the middle reaches of the Yellow and Yangtze Rivers. Accordingly, it is necessary to accelerate digital technology integration with the logistics industry and formulate differentiated development strategies. This study provides a theoretical foundation for exploring the relationship between digital technology and logistics resilience, as well as policy recommendations.